RELATIVISME KONSEPTUAL L . WITTGENSTEIN DAN IMPLIKASI EPISTEMOLOGISNYA - J. Sudarminta (Litbang STFT Widya Sasana Malang, 2003)
Lately, conceptual relativism has been quite influential in epistemology, philosophy of science, and especially in social sciences and cultural studies. This is partly because since 1980’s there has been a growing influence of works in linguistic theories, structuralism and post-structuralism to the methodology of social sciences and cultural studies. This article is attempt to study: (1) What is conceptual relativism and what are its basic tenets?; (2) Is there any connection between conceptual relativism and later Wittgenstein’s language games theory?; and (3) How will we critically assess this view? It will be shown that, despite its important contribution to our better understanding of the relationship between language, thought and reality, conceptual relativism as an epistemological position is basically inadequate.